Predictive Value of the Triglyceride to High-Density Lipoprotein Cholesterol Ratio for All-Cause Mortality and Cardiovascular Death in Diabetic Patients With Coronary Artery Disease Treated With Statins - Wang, Le; Cong, Hongliang; Zhang, Jingxia; Hu, Yuecheng; Wei, Ao; Zhang, Yingyi; Yang, Hua; Ren, Libin; Qi, Wei; Li, Wenyu (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Studies have highlighted the role of the triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio on subsequent cardiovascular events. However, the association of the TG/HDL-C ratio with survival outcomes in diabetic patients with coronary artery disease (CAD) treated with statins remains unknown. This study aimed to assess the predictive value of the TG/HDL-C ratio for all-cause mortality and cardiovascular death in diabetic patients with CAD treated with statins. Methods: The data of patients with type 2 diabetes and angiographically-confirmed CAD who were undergoing statin therapy and visited Tianjin Chest Hospital between January 2016 and September 2016 were retrospectively collected. The patients were categorized based on the baseline TG/HDL-C ratio tertile. Kaplan-Meier analysis and multivariate Cox proportional hazard regression were applied to assess the role of the TG/HDL-C ratio in predicting all-cause mortality and cardiovascular death. Results: A total of 2,080 patients were included. During the 4-year follow-up, 209 patients died, 136 of whom from cardiovascular death. The Kaplan-Meier analyses showed that an increased TG/HDL-C ratio was associated with an increased risk of all-cause mortality (P<0.001) and cardiovascular death (P<0.001). The multivariate cox hazard regression analysis revealed a similar effect of the TG/HDL-C ratio on the risk of all-cause mortality (P=0.046) and cardiovascular death (P=0.009). The role of the TG/HDL-C ratio in predicting all-cause mortality and cardiovascular death was similar among all subgroups (P>0.050). For all-cause mortality, the TG/HDL-C ratio significantly improved the C-statistic from 0.799 to 0.812 (P=0.018), and the net reclassification index (NRI) and integrated discrimination index (IDI) were 0.252 (95% CI: 0.112-0.392; P<0.001) and 0.012 (95% CI: 0.003-0.022; P=0.012), respectively. Similarly, for cardiovascular death, the TG/HDL-C ratio significantly improved the C-statistic from0.771 to 0.804 (P<0.001), and the NRI and IDI were 0.508(95% CI: 0.335-0.680; P<0.001) and 0.033 (95% CI: 0.015-0.050; P<0.001). Conclusion: TG/HDL-C ratio might be useful for predicting all-cause mortality and cardiovascular death in diabetic patients with CAD treated with statins.